Pengaruh Interaksi Guru dalam Platform Digital terhadap Keterlibatan Belajar Siswa Sekolah Dasar - Sonhaji, Sonhaji; Kusumastuti, Fitri Anisa (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The advancement of technology in education demands changes in instructional strategies, including at the elementary school level. Teacher interaction in digital learning plays a crucial role in fostering student engagement. This study aims to examine the influence of teacher interaction through digital platforms on elementary school students' learning engagement. The research employed a quantitative approach using an ex post facto method. The subjects were fifth-grade students from a public elementary school actively using digital learning platforms. Data were collected through a closed-ended questionnaire designed around two main variables: teacher interaction and student engagement. Data analysis was conducted using simple linear regression. The results revealed that teacher interaction significantly influences students’ learning engagement in the context of online learning. These findings highlight the importance of active, open, and supportive communication by teachers in digital learning environments. Moreover, consistent interaction quality can enhance students’ motivation and activeness during learning. This study recommends ongoing teacher training in managing effective, engaging, and sustainable digital interaction strategies as part of adapting to digital education in primary schools.Perkembangan teknologi menuntut perubahan strategi pembelajaran, dimana interaksi guru secara digital menjadi kunci keterlibatan belajar siswa sekolah dasar. Penelitian ini bertujuan untuk mengkaji pengaruh interaksi guru melalui platform digital terhadap keterlibatan belajar siswa SD. Pendekatan yang digunakan adalah kuantitatif dengan metode ex post facto. Subjek penelitian adalah siswa kelas V pada salah satu sekolah dasar yang aktif menggunakan platform pembelajaran daring. Data diperoleh melalui angket tertutup yang disusun berdasarkan dua variabel utama, yaitu interaksi guru dan keterlibatan belajar siswa. Analisis dilakukan menggunakan regresi linier sederhana. Hasil penelitian menunjukkan bahwa interaksi guru secara signifikan memengaruhi keterlibatan belajar siswa dalam konteks pembelajaran daring. Temuan ini menunjukkan pentingnya peran guru dalam menciptakan komunikasi yang aktif, terbuka, dan mendukung melalui media digital. Selain itu, kualitas interaksi yang konsisten dapat meningkatkan motivasi dan keaktifan siswa dalam proses belajar. Penelitian ini merekomendasikan perlunya pelatihan guru dalam pengelolaan interaksi daring yang efektif, menarik, dan berkelanjutan sebagai bagian dari adaptasi pendidikan digital di sekolah dasar.